The posterior urethral valves revisited: embryological correlation, clinical classification, and risk stratification of the spectrum - Vivek Parameswara Sarma (SpringerOpen, 2020)
Abstract Background The diagnosis of posterior urethral valves (PUV) encompasses a vast spectrum of disease with variable severity and clinical features. It is vital to understand the extent of developmental insult and to define the different distinct entities grouped together under the diagnostic umbrella of PUV. This would help to determine the severity of the disease, enable better prognostication, and optimize therapy. The objective of this study is to analyze the variable features of PUV and correlate the different manifestations with the embryological development of the urinary system. The possible developmental basis of anomalies in PUV is analyzed, as recognition of the underlying defect would help to determine the severity of the disease. A clinical classification and a risk stratification approach encompassing the spectrum of PUV is proposed, to help define diagnosis and guide prognosis. A combined retrospective and prospective analysis of cases diagnosed as PUV at the tertiary teaching institute over a 5-year period from July 2014 to July 2019 was done. The outcome of selected cases was analyzed, based on the risk group stratification. Results The incidence of major complications during follow-up in each risk group was assessed individually and found to be highest in the high-risk group (92%), which was significantly higher than the other groups. The intermediate risk group was found to have a complication rate of 38%, while the low-risk group had only 12.5% complication rate. The three key concepts addressed in this study pertain to the embryological basis of PUV, the necessity of a clinical subdivision of patients, and the possibility of risk stratification based on clinical criteria. The limited review of institutional series is added to highlight the method of risk stratification and its probable utility. Conclusions The most critical factors to be accounted for in the diagnosis and management of PUV are the definition of disease severity, recognition of systemic complications, and identification of children at risk of progression to ESRD. The proposed developmental defect analysis, description of PUV sequence, clinical classification, and risk stratification approach are only the means to this end of segregating patient groups within the diagnostic spectrum.